THE EFFECT OF VEDOLIZUMAB ON CD8 T CELL REPERTOIRE HOMOGENEITY AND BLOOD-GUT TRAFFICKING IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (26th January 2023) - Williams, Kyle; Shows, Donna; Kongala, Ramya; Hindmarch, Duncan; Clarke, Astrid; Lord, James
Abstract: BACKGROUND: Inflammatory bowel disease (IBD) causes T cell infiltration of the intestinal mucosa, but the heterogeneity of these cells is not understood at a clonal level. The drug vedolizumab is believed to treat IBD by blocking the entry of circulating integrin α4β7+ T cells into the intestinal mucosa. METHODS: We sought to understand the clonal distribution of T cells in IBD and how this is affected by vedolizumab by studying the T cell receptor (TCR) repertoire in CD8+ T cell subsets sorted from blood samples and colon mucosal biopsies via FACS. Inflamed or uninflamed colon segments from 15 ulcerative colitis and 13 Crohn's disease patients were compared to colon biopsies from 11 people without IBD. In peripheral blood, we profiled purified α4β7+, α4β7- effector/memory, CD45RA+ terminal effector/memory (TEMRA) CD8 T cells, and mucosal-associated invariant T (MAIT) cells. In a separate cohort of 13 IBD patients, samples were obtained before and during vedolizumab therapy to determine its effect on the diversity and overlap of the TCR repertoires of blood and colon CD8+ T cells. RESULTS: CD8 TCR diversity in the mucosa and peripheral blood did not correlate with inflammation. Repertoire overlap between any two anatomically distinct locations of a person's colon was consistently high, though often lower between inflamed and uninflamed sites. CD8 TCR repertoire overlap was also seen between the colon and each peripheral blood subpopulation studied, with the highest overlap seen for integrin α4β7+ T cells and the lowest for MAIT cells. Inflamed tissue overlapped more than uninflamed with each blood subpopulation. Surprisingly, vedolizumab did not affect the degree of overlap between colon CD8+ T cells and circulating α4β7+ CD8 T cells, nor their TCR diversity, regardless of treatment efficacy. Indeed, flow cytometry revealed no relative depletion of effector/memory T cells in the colons of vedolizumab recipients. Instead, vedolizumab caused the depletion of rare naïve mucosal T cells and dendritic cells (DC) from the colonic mucosa. CONCLUSIONS: CD8 T cell clones are spread homogenously throughout the colon. Although TCR repertoire overlap is greater within than between inflamed and uninflamed colon segments, a similar diversity of TCRs in both argues against local clonal expansion being the main source of excess T cells in inflamed mucosa. Rather, our data reveal increased TCR overlap between blood and inflamed mucosa to support the significance of T cell trafficking in IBD pathogenesis, particularly concerning experienced α4β7+ T cell populations. However, we surprisingly found neither gross nor clonal evidence that blockade of this trafficking is the mechanism by which vedolizumab treats IBD, instead finding only naïve T cells and DC to be depleted from the colonic mucosa in response to vedolizumab.